Hepatic and Plasma Endothelin‐1 in Dogs with Chronic Hepatitis. (14th March 2017) - Sakamoto, Y.; Sakai, M.; Watari, T.
Abstract : Background: Endothelin (ET)‐1 is a 21‐amino‐acid peptide with potent vasoactive properties, which increases intrahepatic resistance in patients with chronic hepatitis (CH) or cirrhosis. ET‐1 concentrations have not been investigated in dogs with CH. Hypothesis/Objectives: This study compared hepatic and plasma ET‐1 levels in healthy dogs and in dogs with CH, and examined the relationship between the plasma ET‐1 level and portal vein pressure in dogs with CH. Animals: Fourteen healthy dogs and twenty dogs with CH were used in this study. Methods: Prospective case‐control study. Hepatic ET‐1 mRNA expression was determined by real‐time reverse transcription polymerase chain reaction, and hepatic and plasma ET‐1 levels were assessed using ELISA. Splenic pulp pressure (SPP), as an indicator of portal vein pressure, was measured laparoscopically. Results: Hepatic ET‐1 mRNA levels were 3.7 times higher in dogs with CH than in healthy dogs ( P = .008). The median hepatic and plasma ET‐1 protein levels were significantly higher in dogs with CH than in healthy dogs (13.20 pg/mg wet liver vs. 3.42 pg/mg wet liver, P = .004, and 0.99 pg/mL vs. 0.71 pg/mL, P = .013, respectively). Moreover, there was a weak but significant correlation between plasma ET‐1 level and SPP in dogs with CH ( P = .036; r s = 0.53). Conclusions and clinical importance: The results indicate that ET‐1 might play an important role in the pathogenesis of portal hypertension caused by CH.